Breaking the pain barrier: how suzetrigine and selective sodium channel blockers are reshaping the future of opioid-free analgesia - Kaniak, Aleksandra; Andrzejewska, Julia; Forszt, Kacper; Gawron, Eliza; Hauzer, Paula; Kulicka, Natalia; Ogórek, Agata; Osowska, Alicja; Zielska, Julianna; Ziółkowska, Dominika (Quality in Sport, 2025)
Introduction: Pain is a complex clinical challenge, with opioids traditionally used despite the risks of dependency and overdose. The need for safer alternatives has led to growing interest in voltage-gated sodium channels, particularly NaV1.7, NaV1.8, and NaV1.9, as targets for non-opioid pain management. The recent FDA approval of suzetrigine, a selective NaV1.8 inhibitor, marks a significant step forward in opioid-free pain treatment. Aim of the Study: This review aims to explore the role of voltage-gated sodium channels in pain transmission and evaluate their potential as therapeutic targets, highlighting suzetrigine as a promising new analgesic. Material and Methods: This review, based on data from PubMed, Google Scholar, and ClinicalTrials.gov, focuses on the pathophysiological role of sodium channels in pain and the latest research on selective blockers. Results: NaV1.7, NaV1.8, NaV1.9 play critical roles in various pain states. While clinical trials targeting NaV1.7 have delivered disappointing results, selective inhibition of NaV1.8 has shown greater promise, with suzetrigine demonstrating significant efficacy in clinical trials. Conclusion: Targeting voltage-gated sodium channels, especially NaV1.8, offers a promising strategy for the development of effective and safer analgesics. Suzetrigine marks a milestone, paving the way for a new class of non-opioid pain therapies with broad clinical application.